Cross‐Validation of IFN‐γ Elispot Assay for Measuring Alloreactive Memory/Effector T Cell Responses in Renal Transplant Recipients. Issue 7 (13th June 2013) - Bestard, O.; Crespo, E.; Stein, M.; Lúcia, M.; Roelen, D. L.; de Vaal, Y. J.; Hernandez‐Fuentes, M. P.; Chatenoud, L.; Wood, K. J.; Claas, F. H.; Cruzado, J. M.; Grinyó, J. M.; et al.
Abstract: Assessment of donor‐specific alloreactive memory/effector T cell responses using an IFN‐γ Elispot assay has been suggested to be a novel immune‐monitoring tool for evaluating the cellular immune risk in renal transplantation. Here, we report the cross‐validation data of the IFN‐γ Elispot assay performed within different European laboratories taking part of the EU RISET consortium. For this purpose, development of a standard operating procedure (SOP), comparisons of lectures of IFN‐γ plates assessing intra‐ and interlaboratory assay variability of allogeneic or peptide stimuli in both healthy and kidney transplant individuals have been the main objectives. We show that the use of a same SOP and count‐settings of the Elispot bioreader allow low coefficient variation between laboratories. Frozen and shipped samples display slightly lower detectable IFN‐γ frequencies than fresh samples. Importantly, a close correlation between different laboratories is obtained when measuring high frequencies of antigen‐specific primed/memory T cell alloresponses. Interestingly, significant high donor‐specific alloreactive T cell responses can be similarly detected among different laboratories in kidney transplant patients displaying histological patterns of acute T cell mediated rejection. In conclusion, assessment of circulating alloreactive memory/effector T cells using an INF‐γ Elispot assay can be accurately achieved using the same SOP, Elispot bioreader and experienced technicians in kidney transplantation. Abstract : Using a set of standardized operating procedures investigators can accurately assess circulating alloreactive memory/effector T cells in the context of kidney transplantation. See more in the CTOT series, pages 1859–1904.